Pengaruh Penggunaan Jaminan Bank Dan Asuransi Terhadap Keberhasilan Klaim Dalam Pekerjaan Kontruksi Dengan Metode Analytical Hierarchy Process (AHP) - Romadhoni, Al – Hafiz; Prabowo, Yudi Setio (Syntax Literate, 2025)
This study evaluates the effect of the use of bank guarantees and insurance on the success of claims in construction projects in Indonesia using the Analytical Hierarchy Process (AHP) method. Data were obtained from four groups of respondents: contractors, Commitment Making Officials (PPK) of the Cilegon City PUPR Office, insurance companies (PT Askrindo Insurance Kota Serang), and supervisory consultants (Indra Design). The results of the calculation showed that the entire comparison matrix was consistent (CR < 0.1). Of the seven main criteria, design changes gained the highest weight from the perspectives of contractors (0.456), insurance (0.394), and supervisory consultants (0.276), while project completion & time were most dominant for PPK (0.204) and supervisory consultants (0.467). Payments & finances also emerged as important factors with weights between 0.125–0.276. Meanwhile, the weight of bank guarantees and insurance was relatively low in the three technical perspectives (0.041–0.079) but was the main focus of the insurance perspective (0.482). At the alternative level of the field, poor contract clauses and delays in IMB licensing both occupy a maximum weight (1,000) for contractors and PPKs, confirming the importance of the administrative aspect. These findings confirm that the management of design changes, payment processes, and contract/licensing documentation is key to claims mitigation, with bank guarantees and insurance acting as additional financial protection instruments.